Weight maintenance: Self-regulatory factors underpinning success and failure - McKee, H.; Ntoumanis, Nikos; Smith, B. (Routledge, 2013)
Objectives: To investigate the differences in the contributing factors involved in weight maintenance success and failure. Design: Semi-structured interviews were conducted with both successful and unsuccessful weight maintainers. Eighteen participants were recruited (16 women), nine of who had lost 10% of their body weight and maintained this weight for a minimum of 12 months (Maintainers), and nine individuals who met the above criteria for weight loss but had subsequently regained their weight (Regainers). A thematic analysis was employed to compare the differences between the two groups. Results and conclusions: Two main themes highlighted the differences between the two groups, these were: goal regulation and self-control. Within these overarching themes, successful weight maintenance was related to the following subthemes: long-term, realistic goal setting, consistent use of routines and self-monitoring, avoiding deprivation and effective coping skills. Unsuccessful maintenance was related to short-term unrealistic goal setting, inconsistent routines and self-monitoring, experiencing deprivation and poor coping skills. These factors are explained in terms of the interrelationships that they have on one another and their subsequent impact on weight maintenance success or failure.